2019
DOI: 10.1007/s10113-019-01517-4
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge co-production in protective spaces: case studies of two climate adaptation projects

Abstract: Knowledge co-production, a mode of research including contributions both from academic and non-academic actors, is a promising approach for climate adaptation research in order to produce knowledge that supports the development of local and regional adaptation policies. However, such a local and practical focus may be ill-aligned with the global ambitions of academic participants. The differences between performance criteria of academic and non-academic partners make knowledge coproduction unlikely to emerge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Contestation is almost inevitable as different epistemologies and ontologies come together (Turnhout et al, 2020). All stakeholders participating in the process will be conditioned by norms, values and performance criteria (Boon et al, 2019). These will likely affect their expectations and create challenges in the process (Boon et al, 2014).…”
Section: Explicitly Recognising Power In Co-productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contestation is almost inevitable as different epistemologies and ontologies come together (Turnhout et al, 2020). All stakeholders participating in the process will be conditioned by norms, values and performance criteria (Boon et al, 2019). These will likely affect their expectations and create challenges in the process (Boon et al, 2014).…”
Section: Explicitly Recognising Power In Co-productionmentioning
confidence: 99%
“…Researchers, and their employing organisations, might expect rigorous scientific research that can be published in high impact journals, for example, whilst governments or communities might be more concerned with immediate, context-appropriate solutions to challenges. Proactively identifying a protection strategy is important to ensure that such rigidities do not curtail the potential success of the co-production effort: for example, through shielding against the pressures, nurturing knowledge development and promoting empowerment that enables influence over the contexts (Boon et al, 2019).…”
Section: Explicitly Recognising Power In Co-productionmentioning
confidence: 99%
“…Although transdisciplinary research is often suggested as a suitable approach in sustainability literature, there are also barriers and challenges associated with it. Because the principles of transdisciplinary research do not readily match with the institutional context of academic research, it requires protection in the form of nurturing, shielding or empowerment (Boon et al 2019). There is a large body of literature elaborating on the barriers for transdisciplinary research.…”
Section: Transdisciplinarity and Sustainability Programmesmentioning
confidence: 99%
“…The ideas were to challenge the classical representation of knowledge creation coming before practices and their relative disconnection from development's trajectory. Today, various types of interactions have been identified [64], and the experience gained through case studies [9,11,12,39,[65][66][67][68] gave insights into the mechanisms and the components of "successful" collaboration practices. First, trust-based relationships and frequency of interactions between researchers and practitioners (informal meeting, workshops, and seminars) is a cornerstone for the construction of strategic coalitions able to engage in societal issues.…”
Section: Transdisciplinary Collaborative Processmentioning
confidence: 99%